Germinal centre CD4+ T cells are an important site of HIV replication in vivo - Hufert, Frank T.; van Lunzen, Jan; Janossy, George; Bertram, Sylvia; Schmitz, Jörn; Haller, Otto; Racz, Paul; von Laer, Dorothee (AIDS (London), 1997)
CD4+ T cells are the main target for HIV. However, the highest HIV antigen concentration in infected subjects accumulates on the cell surface of follicular dendritic cells in the germinal centres of the lymphoid tissue. Germinal centres contain a T-helper cell subset which expresses CD57 molecules. Here we analysed virus replication and viral load in CD57+CD4+ germinal centre T cells and in the CD4+ T cells found mostly outside germinal centres (CD57-CD4+). Peripheral blood mononuclear cells and lymph-node cells were prepared, stained for CD4 and CD57 and purified by FACS. Defined cell numbers of CD4+CD57+ cells and CD4+CD57- cells were sorted directly into polymerase chain reaction (PCR) tubes by FACS, equipped with an automated cell deposition unit and analysed by PCR to detect proviral DNA. Based on Poisson distribution, the expected level of infection was calculated. Viral replication was determined by amplifying double-spliced, single-spliced, and full-length transcripts of HIV using serially diluted cDNA of the FACS-sorted cells. An up to 10-fold higher frequency of infected cells was found in the CD57+CD4+ germinal centre T cells compared with CD57-CD4+ T cells. Furthermore, active viral replication was detected almost exclusively in the CD57+CD4+ T cells. The CD57+CD4+ germinal centre T cells are one of the sites of HIV infection and replication that may play a pivotal role in the pathogenesis of HIV infection.